Analysis of paediatric drowning deaths in Washington State using the child death review (CDR) for surveillance: what CDR does and does not tell us about lethal drowning injury. (27th January 2011) - Quan, Linda; Pilkey, Diane; Gomez, Anthony; Bennett, Elizabeth
Abstract : Background: Drowning is second cause of paediatric injury death in Washington State. Child death review (CDR) data provide the unique opportunity to identify regional risk factors and opportunities for drowning prevention. Methods: CDR teams' data for drowning deaths of children <18 years between 1999 and 2003 were analysed for victim and event characteristics, and existing prevention/protective factors. A working group made data driven recommendations. Subsequent interventions were noted. Results: Drowning death rates were significantly higher among Asian Pacific Islander children (3.3 per 100 000). Disproportionately, 32% of deaths involved families with prior child protective services (CPS) referrals. Most deaths (73%) occurred in open water; the proportion in open water increased from 42% of <5-year-olds, 83% of 5–9-year-olds, to 90% of 10–17-year-olds. Thirty per cent drowned at parks; 29% drowned in residential settings. Pre-drowning activity for 42% was swimming or playing in the water. Alcohol and drug use were low. Neglect/poor supervision was considered a factor in 68% (21/31) of the deaths of children <5 years of age. State CDR recommendations led to the development of a drowning prevention campaign targeted to an Asian American community, intra-agency changes resulting in reinstatement of lifeguard staffing and addition of lifejacket loaner programmes, collaboration with state commissions to enforce a state pool fencing ordinance, and model legislation prohibiting swimming in dangerous waterways. Conclusion: CDR data collection and review process was an effective surveillance tool. It identified specific regional high risk groups and sites for drowning prevention and led to recommendations and implementation of effective local and state injury prevention interventions.